Optimization of foam-filled double ellipse tubes under multiple loading cases. (September 2016) - Gao, Qiang; Wang, Liangmo; Wang, Yuanlong; Guo, Fuxiang; Zhang, Zunzhi
Highlights: We proposed a novel foam-filled double ellipse (F-DET) tube. The crashworthiness of the foam-filled double ellipse tube under multiple loading cases was considered. The design of experiments (DOE) method provided the means to select the sampling points. The multiobjective particle swarm optimization (MOPSO) algorithm was used to optimize the F-DET tube about the radial rate, wall thickness and foam density. Abstract: In this paper, a novel foam-filled double ellipse tube (F-DET) is proposed. First, the circle and ellipse tubes with three different configurations(hollow, foam-filled, double foam-filled) are investigated under axial and oblique impact by using the nonlinear finite element code LS-DYNA. The numerical results showed that the F-DET tube has the best crashworthiness performance than tubes with other configurations. Then to optimize the F-DET tube, the Kriging model about the radial rate f, thickness of wall t and foam density ρf is constructed. Based on the Kriging model, the multiobjective particle swarm optimization (MOPSO) algorithm is utilized to achieve the optimized F-DET tube, foam-filled ellipse(F-ET) tube and foam-filled double circle(F-DCT) tube on the maximizing specific energy absorption (SEA) and minimizing peak crush force (PCF) under multiple loading angles. It can be found that the F-DET tube has better crashworthiness performance than F-ET tube and F-DCT tube. This indicates F-DET tube can be a potential energy absorber under the multiple loading cases.